Variação fenológica dos frutanos e caracterização parcial de sacarose: sacarose frutosiltransferase (1-SST), frutano exohidrolase (1-FEH) e invertase (INV) em órgãos subterrâneos de Chresta exsucca DC. (Asteraceae) - Santos, Camila Silva dos (2017)
Climatic seasonality is a factor of great influence in Cerrado plants. In phases of high energetic demand, carbohydrate accumulation becomes an important resource for the maintenance of plants in adverse environmental conditions, such as drought, cold and fire. Thus, the study of enzymes of carbohydrate metabolism is important in understanding metabolic strategies used by these plants. Chresta exsucca has inulin-type fructans and a distinct phenological profile compared to other Asteraceae species from Cerrado. This species flowers in the dry season and resprouting occurs throughout the year. The objective of this work was to verify the carbohydrate variations in the underground organs of C. exsucca in different phenological phases; to verify the optimal conditions for enzymatic activity of sucrose: sucrose fructosyltransferase (1-SST), fructan exohydrolase (1-FEH) and invertase (INV) and to analyze 1-FEH activity in different phenological phases of this species. Total soluble carbohydrate extraction and quantification were performed and the ratio of oligosaccharide: polysaccharide was <1 in senescence. Enzymatic characterization was carried out in different conditions of time, temperature, pH and substrate concentration. The enzymatic conditions for fructan metabolism in C. exsucca resemble other Asteraceae species. The central rotational compound design for 1-FEH showed that reaction time and pH factors influenced 1-FEH activity in C. exsucca. Resprouting had higher 1-FEH activity compared to other phenological phases. Therefore, fructans stored in the underground organs of C. exsucca, as well as the characteristics of fructan enzymes are essential for maintenance of this plant, resulting in constant resprouting and intense reproductive phase, even in the dry season.